2019
DOI: 10.1136/bmjopen-2019-030912
|View full text |Cite|
|
Sign up to set email alerts
|

Randomised controlled trial of gradual antipsychotic reduction and discontinuation in people with schizophrenia and related disorders: the RADAR trial (Research into Antipsychotic Discontinuation and Reduction)

Abstract: IntroductionAntipsychotic medication is effective in reducing acute symptoms of psychosis, but it has a range of potentially serious and debilitating adverse effects and is often disliked by patients. It is therefore essential it is only used when benefits outweigh harms. Although multiple trials conducted with people with schizophrenia indicate an increased risk of relapse in the short-term following abrupt antipsychotic discontinuation, there is little evidence about the long-term outcome of a gradual proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 53 publications
0
31
0
Order By: Relevance
“…The algorithm does not recommend discontinuation of antipsychotics for the following reasons. First, it is reported that the discontinuation of antipsychotics is associated with a higher risk of relapse even in first‐episode schizophrenia or psychosis (Kishi et al., 2019 ; Leucht et al., 2012 ), several studies are ongoing to address this topic (Begemann et al., 2020 ; Liu et al., 2021 ; Moncrieff et al., 2019 ; Stürup et al., 2017 ; Weller et al., 2019 ). Second, there are no established clinical predictors for successful discontinuation of antipsychotics (Bowtell et al., 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…The algorithm does not recommend discontinuation of antipsychotics for the following reasons. First, it is reported that the discontinuation of antipsychotics is associated with a higher risk of relapse even in first‐episode schizophrenia or psychosis (Kishi et al., 2019 ; Leucht et al., 2012 ), several studies are ongoing to address this topic (Begemann et al., 2020 ; Liu et al., 2021 ; Moncrieff et al., 2019 ; Stürup et al., 2017 ; Weller et al., 2019 ). Second, there are no established clinical predictors for successful discontinuation of antipsychotics (Bowtell et al., 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…From a preventative approach, the optimal tapering regime to minimise the risk of withdrawal symptoms has also not been explored empirically; however, studies are underway. 93 Whilst a patient-rated scale to measure the success of antipsychotic and antidepressant discontinuation has recently been developed, 94 the scale does not differentiate between the withdrawal symptoms described in this review, which may also be present with other psychotropics. 11 Finally, the role of medication to prevent and treat clozapine-withdrawal symptom is largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…This review is part of a wider NIHR funded programmethe RADAR trial on antipsychotic medication reduction. LG, NC and JM are also affiliated with the RADAR trial [21] and members of he trial's LEAP (Lived Experience Advisory Panel), which included mental health service users and carers, were involved in discussing the initial aims of the study and reviewing theories on two occasions.…”
Section: Methodsmentioning
confidence: 99%